DA’WAH IN SOUTH AFRICA: Its Link to Governance and Democracy - Dadoo, Yousuf (Universitas Islam Negeri Alauddin Makassar, 2014)
The present article constitutes an update on the findings of earlier researchers. Its strong point lies in its interrogation of issues by employing social science theories of power in addition to theories of religion at appropriate places. In the process, triumphs and problems relating to da‘wah are revealed. There is also the incongruity between the commitments demanded by Islam and the existential truth of Muslims. This applies particularly to governance and democracy issues. Despite shortcomings, da‘wah continues apace. Possible solutions to these problems are presented at the end of this article.